2006
DOI: 10.1614/wt-05-135.1
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides for Weed Control in Blessed Thistle (Silybum Marianum)

Abstract: Blessed thistle is an important medicinal crop in Europe and recently has become more significant in North America. A limiting factor in blessed thistle production is weed interference. Field experiments were conducted near Plovdiv, Bulgaria, to study the effect of selected herbicides on weed control, crop productivity, and crop quality. Seed yields of blessed thistle were increased with metribuzin alone at 0.5 kg ai/ha, pendimethalin alone 1.32 kg ai/ha, pendimethalin at 1.32 kg ai/ha plus metribuzin at 0.5 k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Milk thistle, also known as blessed thistle, has become one of the most widely grown and economically viable medicinal plants in parts of Europe, including Bulgaria (Zheljazkov et al. 1996), and is being evaluated as a crop in Canada (Omidbaigi & Nobakht 2001; Zheljazkov et al. 2006).…”
Section: Economic Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Milk thistle, also known as blessed thistle, has become one of the most widely grown and economically viable medicinal plants in parts of Europe, including Bulgaria (Zheljazkov et al. 1996), and is being evaluated as a crop in Canada (Omidbaigi & Nobakht 2001; Zheljazkov et al. 2006).…”
Section: Economic Importancementioning
confidence: 99%
“…(2007) reported that milk thistle control in wheat ranged from 90–94% with chlorsulfuron at 10.5 g ai ha −1 , metsulfuron plus sulfosulfuron at 36 g ai ha −1 , or bromoxynil plus MCPA at 560 g ai ha −1 . Zheljazkov et al. (2006) reported that bentazon at 0.96 kg ai ha −1 suppressed milk thistle growth and seed production.…”
Section: Managementmentioning
confidence: 99%
“…Milk thistle is an important medicinal crop in Europe and has recently become more significant in North America (Zheljazkov et al, 2006). The medicinal compounds of value are found in the seeds of the plant.…”
Section: Introductionmentioning
confidence: 99%
“…), fennel (F. vulgare Mill. ), sage (Salvia officinalis L.), savory (Satureja officinalis L.), and thyme (Thymus officinalis L.) (Kothari et al 1989;Pank 1992;Zheljazkov et al 1996;Zheljazkov et al 2006). Following these authors, if phytotoxic effects were avoided, the use of pendimethalin, fluchloralin, and other chemicals did not affect seed or oil yields or oil quality.…”
Section: Introductionmentioning
confidence: 99%